Impact of alternative reimbursement strategies in the new cooperative medical scheme on caesarean delivery rates: a mixed-method study in rural China - Huang Kun; Tao Fangbiao; Bogg Lennart; Tang Shenglan (BMC, 2012)
Abstract Background The rate of caesarean delivery (CD) in rural China has been rapidly increasing in recent decades. Due to the exorbitant costs associated with CD, paying for this expensive procedure is often a great challenge for the majority of rural families. Since 2003, the Chinese government has re-established the New Cooperative Medical Scheme (NCMS), aimed to improve the access of essential healthcare to rural residents and reduce financial burden owing to high out of pocket payments. This paper seeks to test the hypothesis that NCMS may provide service users and providers with financial incentives to select CD. It also assesses the effect of different health insurance reimbursement strategies of NCMS on CD rates in rural China. Methods Mixed quantitative and qualitative methods were adopted for data collection. Two cross-sectional household surveys were conducted with women having babies delivered in 2006 and 2009; 2326 and 1515 women, respectively, from the study sites were interviewed using structured questionnaires, to collect demographic and socio-economic data, maternal and child care characteristics and health-related expenditures. Focus group discussions (FGDs) and in-depth key informant interviews (KIIs) were undertaken with policy makers, health managers, providers and mothers to understand their perceptions of the influence of NCMS on the choices of delivery mode. Results The CD rates in the two study counties were 46.0 percent and 64.7 percent in 2006, increasing to 63.6 percent and 82.1 percent, respectively, in 2009. The study found that decisions on the selection of CD largely came from the pregnant women. Logistic regression analysis, after adjusting for socio-economic, maternal and fetal characteristics, did not indicate a significant effect of either proportional reimbursement or fixed amount reimbursement on the choice of CD for both study years. Interviews with stakeholders reflected that different reimbursable rates for CD and vaginal deliveries did not have a significant effect on controlling the rising CD rate in the study countries. Conclusion NCMS reimbursement strategies adopted in the study counties of China did not have a significant effect on the selection of CD for baby deliveries. The rapid rise of the CD rates of rural China has remained a serious issue. Other effective measures, such as health education to increase awareness of mothers' knowledge, and improving training of health staff in evidence-based delivery care, maybe could do more to promote rational baby delivery in rural China.